A critical approach to the concept of “Penal law of the enemy” - GROSSO GARCÍA, MANUEL SALVADOR (Universidad Santo Tomás, Bogotá-Colombia, 2016)
The article analyses, from a critical perspective and within the framework of criminal policy and the penaldogma, the concept of “Penal Law of the Enemy”. Additionally, the text links this concept to the LatinAmerican reality, taking the case of Colombia as the point of reference.